Perbandingan Makna Pada Peribahasa Yang Menggunakan Kata “Hati” Dalam Bahasa Mandarin Dan Bahasa Indonesia - Sinar Anwar; Silviani Silviani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Language is unique and universal. Unique means that every language has the same characteristics that are owned by every language in the world and universal means that it has its own characteristics that are not owned by other languages. This study aims to compare the similarities and differences in meaning found in Chinese proverbs and Indonesian proverbs that use the word